SOSIALISASI PETAI (PARKIA SPECIOSA HASSK) DI DESA KENAYAN, NGEMPLAK, KABUPATEN SLEMAN : SOSIALISASI PETAI (PARKIA SPECIOSA HASSK) DI DESA KENAYAN, NGEMPLAK, KABUPATEN SLEMAN - Bambang Pujiasmanto; Sulandjari Sulandjari; Pardono Pardono; Eddy Triharyanto (Lembaga Penelitian dan Pengabdian Masyarakat, 2022)
Petai (Parkia speciosa Hassk) is a horticultural plant as a vegetable that is beneficial for health. Petai can help treat digestion to help neutralize stomach acid. Petai has a fairly high nutritional content, namely vitamin A, vitamin C, calcium, and iron so it is necessary to make efforts to cultivate petai plants as a business opportunity. Petai trees grow and develop in Kenayan village, namely on vacant village treasury land, cliff land and yard. This service aims to increase the knowledge of farmers in the cultivation of petai. Service activities are carried out using a participatory method. The service activities were carried out 4 times, namely counseling on petai cultivation related to the provision of plant materials, care, harvesting and post-harvest, socialization about the propagation of petai plants by grafting, handing over assistance of a number of grafted petai seeds in the hope of fruiting more quickly and assistance in socialization about petai cultivation. Public knowledge about petai cultivation and how to propagate petai by grafting has increased. Grafting is one way to improve the quality of plants by attaching a piece of tree bark with buds from the scion to a slice of the bark of another tree from the rootstock so that it grows together to form a new plant. Planting petai in the yard of the house is an alternative as an herbal treatment to improve health and increase family income.